PERBANDINGAN TINGKAT KESEHATAN BANK SEBELUM PANDEMIK DAN MASA PANDEMIK COVID 19 DENGAN MENGGUNAKAN METODE RGEC PADA PT BANK NEGARA INDONESIA TBK PERIODE 2018 – 2020 - Khristina Sri Prihatin; Aqdiah Aqdiah (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
This study aims to compare the soundness level of banks using the RGEC (Risk Profile, Good Corporate Governance, Earning, Capital) method at PT. Bank Negara Indonesia (BNI), Tbk before the pandemic (2018-2019) and during the Covid-19 pandemic (2020). The type of research used is a type of quantitative research (quantitative descriptive). The data used in this study is secondary data, namely data from Bank Negara Indonesia, consisting of Financial Position Reports, Profit and Loss Reports and Governance Implementation Reports for 3 periods, namely 2018-2020. The results showed that the NPL ratio was 1.9%; 2.3%; 4.2% rated very healthy, healthy and healthy enough to meet the maximum limit of 5%. LDR ratio 88%; 91%; 86% with a very healthy predicate met the maximum limit of 85%. GCG Compost Value 2; 2; 2, healthy predicate. ROA ratio of 2.4%; 2.3%; 0.6% is considered very healthy for 2018 and 2019, while 2020 is considered quite healthy due to the pandemic. NIM ratio of 4.7%; 4.6%; 4.5% have a very healthy rating. CAR ratio of 18.5%; 19.7%; 16.8% rated very healthy for 3 consecutive years. Based on the results of the analysis, it was concluded that the use of the RGEC method to measure the health level of a bank before the pandemic and during the Covid 19 pandemic at Bank BNI experienced a decrease in the NPL ratio and ROA ratio so that in 2020 it only received the HEALTHY ENOUGH predicate during the Covid 19 pandemic.